Theoretical and experimental investigation of a Solar Free-Piston Stirling Engine (FPSE) using a flexible bellow for water pumping/power generation - Shalak, Mohamed (2022)
Fossil fuels are the primary energy source globally and currently represent more than 80% of the overall energy consumption. Fossil fuels such as natural gas, oil and coal remain the principal fuels for supply and off-grid power generation in remote areas. Concerns over the negative environmental impact of greenhouse gases emission have shifted toward deploying and developing renewable and low carbon energy technologies. In the last decades, many sustainable and clean energy alternatives have been exploited to make energy and power generation clean and affordable to mitigate the negative impact of fossil fuels on the environment. The Stirling engine is considered one of the most promising solutions of sustainable power technologies to generate electricity from external heat sources.